Minoische Bild-Räume Neue Untersuchungen zu den Wandbildern des spätbronzezeitlichen Palastes von Knossos - Günkel-Maschek, Ute (Heidelberg University Publishing (heiUP), 2020)
This volume presents a new analysis of the wall paintings discovered over a hundred years ago in one of the most important centres of Minoan culture, the palace at Knossos. Introducing the theoretical concept of Bild-Raum, a relational construct linking pictorial elements with humans, actions and places, the aim is to produce new insights as to the types of rituals, ideas and people which can be related with individual parts of the palace based on the decoration painted on the walls. The images and architecture of three key areas of the palace are studied in broad detail, improving our understanding of performances and people involved and their role within the complex history of the Late Bronze Age palace at Knossos.; Der vorliegende Band stellt eine neue Analyse der Wandbilder vor, die vor über 100 Jahren an den Wänden des bedeutendsten Zentrums der minoischen Kultur, des Palastes von Knossos, gefunden wurden. Im Mittelpunkt der Untersuchungen steht der Begriff des Bild-Raums, eine theoretisch begründete, relationale Verknüpfung von Bildelementen, Menschen, Handlungen und Orten. Das Ziel ist es, basierend auf dem Wanddekor einzelner Gebäudetrakte ein besseres Verständnis der einst mit ihnen verbundenen Rituale, Ideen und Personen zu gewinnen. In ausführlichen Fallstudien werden die Bild-Räume dreier bedeutender Palastareale analysiert, rekonstruiert und in ihren spätbronzezeitlichen Kontext gestellt.